The Influence of Corporate Culture on Employee Performance at Daima Hotel Padang - Yulia Asnella; Arif Adrian (Pt. Threeple Herphi Educate, 2025)
This study aims to evaluate the effect of corporate culture on employee performance at Daima Hotel Padang. Employing a quantitative causal-associative design, data were collected from all 60 hotel employees using a saturated sampling technique and analyzed through simple linear regression with SPSS version 26.0. The results reveal a regression coefficient of 0.286 with a significance value of 0.001 (p < 0.05), indicating that corporate culture has a positive and statistically significant influence on employee performance. The coefficient of determination (R²) of 0.182 suggests that corporate culture accounts for 18.2% of the variance in employee performance, while the remaining 81.8% is explained by other factors not examined in this study. These findings underscore the strategic importance of cultivating a strong organizational culture—characterized by shared values, adherence to Standard Operating Procedures (SOPs), effective communication, and supportive leadership—in enhancing service quality, operational efficiency, and interdepartmental collaboration. The study provides both theoretical contributions, by reinforcing the relevance of organizational culture theory in the hospitality sector, and practical implications, by offering actionable insights for hotel managers to strengthen corporate culture as a means of improving employee performance. Future research is recommended to incorporate additional variables such as job satisfaction, leadership style, and employee engagement, as well as to adopt longitudinal or multi-site designs for broader applicability.